Tigers of the world : the science, politics and conservation of panthera tigris - Tilson, Ronald Lewis; ScienceDirect eBooks (Norwich, N.Y. : William Andrew ; Oxford : Elsevier Science [distributor], 2008)
The second edition of Tigers of the World explores tiger biology, ecology, conservation, management, and the science and technology that make this possible. In 1988 when the first edition was published, tiger conservation was still in its infancy, and two decades later there has been a revolution not only in what is known, but how information about tigers is obtained and disseminated. In the fast changing world of conservation there is a great need to summarize the vast and current state-of-the-art, to put this into historical perspective, and to speculate in what yet remains to be done. Tigers of the World, 2nd Edition fulfills this need by bringing together in a unique way the world's leading tiger experts into one volume. Despite the challenges ahead, there are bright spots in this story, and lessons aplenty not only for tiger specialists but large carnivore specialists, conservation biologists, wildlife managers, natural resource policy makers, and most importantly the caring public. It is through broad public understanding and support in Asia, North America, and Europe that will have the greatest impact on tigers over the long term. With this in mind, the book is novel in its presentation of information using images, indigenous art and poetry, anecdotes, maps and other images to engage and inform. Side bars and text boxes focus on important concepts and debates and help to balance different perspectives and opinions. There is no other book which equally benefits both the scientific and general audiences. *Comprehensive look at the past twenty years from the world's leading tiger experts on the biology, politics, and conservation of this species. *Discusses that latest and vast methods used to disseminate and obtain information needed for conservation and care of this species. *Excellent opportunity for upper-level and graduate courses in conservation biology, wildlife management, and veterinary programs. *The world's leading tiger experts review recent advances and debates in tiger genetics and ecology, research methods, management and policy, poaching and trade, captive breeding and farming, conservation, and the status of Asia's last wild tigers.
Current Knowledge of Wild Tigers * The Evolution of Tiger Extinction * What is a Tiger? * The Evolution and Taxonomy of Tigers * The Conservation and Management of Tigers * Tigers and Landscapes * Tigers and Conflict * Tigers and Trade * Tigers and the Future: Reintroducing Tigers and Restoring Tiger Habitat * Tools for Tiger Research and Conservation * Research and Monitoring: Field Methods for Tiger Conservation Biology * Recruiting, Training, and Inserting Anti-Poaching Teams * Linking People, Tigers, and Livelihoods * Techniques for Identifying and Managing the Trade in Tiger Parts * Regional Reviews: Science, Conservation, and Politics * Amur Tigers and the Russian Far East * Bengal Tigers and the Indian Subcontinent * Indochinese Tigers and Indochina * South China Tiger * Sumatran Tigers and Indonesia * Captive Tigers * Caring for Tigers in Captivity * Understanding Genetic and Demographic Management of Captive Tigers * Tigers in the Backyard.
Previous edition: Park Ridge, N.J.: Noyes, 1987.
Print version record.
Elsevier
Keywords: Tiger; Tiger -- Ecology; Tiger -- Conservation; Wildlife conservation; Wildlife management; Tiger; Tiger -- Conservation; Wildlife conservation; Wildlife management; Electronic books